IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER GUNA MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA DI PONDOK PESANTREN DAAR EL-QOLAM DESA PASIR GINTUNG KECAMATAN JAYANTI KABUPATEN TANGERANG BANTEN - Khaerul Anam (UNISAN JURNAL, 2024)
This research aims to describe the implementation of character education at the Daar El-Qolam Islamic Boarding School, Tangerang. This research uses a qualitative approach technique with descriptive methods. Therefore, this research is a qualitative descriptive research. Research data was collected through observation, interviews and documentaries. And for data that looks bright, categorization is made using a coding system. Data validity is carried out through the triangulation method. Data were analyzed during and after the study. The results of the research show that in implementing character education at the Daar El-Qolam Tangerang Islamic Boarding School, there are main competencies that are mastered by each teacher, namely; The RPP regulates competencies, curriculum implementation and evaluation. So, the implementation of character education for each lesson is through: creating graduate competency standards (SKL), preparing standards (SK), preparing learning indicators, learning evaluation strategies, implementing all these improvements with supporting and limiting factors. This has a big meaning, it has research implications, namely that every teacher must have professionalism, be a good worker, have fresh functions, and have credible performance. This means that implementing character education is education with aspects of building morals, (ethics-aesthetics), cognition, feelings and psychomotor actions.